FINGERPRINTS TO AUTHENTICATE TRANSACTIONS IN CONTACTLESS CARDS - soleen J. Ibrahim; Ahmad B. Al-Khalil (Science Journal of University of Zakho, 2023)
The contactless bank card is a replica of the old fashion payment methods. The contactless card saves the customer a lot of time and effort because the cardholder can tap the card on the card reader instead of carrying a massive amount of cash or memorizing a long password. The transaction will be done in a few seconds, which is a magnificent technique for a very rush and speedy world like this. However, because the contactless card does not require a PIN or signature, it is vulnerable to different types of attacks, and the card can be used by every single person who has the card, even if they are not the real cardholder. Nevertheless, for each new problem, there is a unique solution. Hence this paper presents an innovative way to overcome this problem by embedding a fingerprint sensor into the contactless card to add an extra level of security by creating a virtual environment giving a contactless card and using a minutiae-based algorithm for fingerprint recognition in this contactless card. The work is evaluated based on accuracy using two metrics, false acceptance rate (FAR) and false rejection rate (FRR), algorithm’s matching time, and transaction time. This work shows a good result regarding the transaction time and the possibility of integrating the fingerprint into the contactless card. It displays how fingerprint image quality and features affect fingerprint authentication results. However, it also shows that minutiae-based techniques are not adequate when the dataset is relatively small and has data with low-quality and/or noisy data.